High incidence of a third head of biceps brachii in females - Luke A. Schwerdtfeger; Michael A. Pascoe; Tod Clapp (Elsevier, 2018)
Incidence rates of a third head of biceps brachii muscle have been shown to vary based on race, sex, and side of the body. Traditionally, males were thought to have higher incidences than females, and the right limb was thought to most frequently contain an additional head of biceps brachii. Additionally, innervation of this third head has been unclear, with musculocutaneous nerve, median nerve, or a combination of both providing nerve supply. Here we present findings of the dissection of 23 cadavers (n = 46 limbs), in which 6 limbs demonstrated a third head of biceps brachii. Of the 6 limbs with a third head, 3 were left and 3 were right limbs, with one cadaver having the extra muscle head bilaterally. Incidence rates in females in the current study were observed to be higher than expected (20.8%), while males showed a 4.5% occurrence. All 6 of the additional heads of biceps brachii observed were innervated by musculocutaneous nerve. Together these data show a higher than expected number of female cadavers with a third head of biceps brachii, equal incidence between sides of the body, and uniform innervation by musculocutaneous nerve. These findings challenge our traditional understanding of the third head of biceps brachii and suggests a need for additional study of this complex anatomical variation. Keywords: Biceps brachii, Third head, Innervation, Sex, Cadaver, Variation